Fabrication of thin ZnO films with wide-range tuned optical properties by reactive magnetron sputtering. (10th January 2018) - Davydova, A; Tselikov, G; Dilone, D; Rao, K V; Kabashin, A V; Belova, L
Abstract: We report the manufacturing of thin zinc oxide films by reactive magnetron sputtering at room temperature, and examine their structural and optical properties. We show that the partial oxygen pressure in DC mode can have dramatic effect on absorption and refractive index (RI) of the films in a broad spectral range. In particular, the change of the oxygen pressure from 7% to 5% can lead to either conventional crystalline ZnO films having low absorption and characteristic descending dependence of RI from 2.4–2.7 RIU in the visible to 1.8–2 RIU in the near-infrared (1600 nm) range, or to untypical films, composed of ZnO nano-crystals embedded into amorphous matrix, exhibiting unexpectedly high absorption in the visible–infrared region and ascending dependence of RI with values varying from 1.5 RIU in the visible to 4 RIU in the IR (1600 nm), respectively. Untypical optical characteristics in the second case are explained by defects in ZnO structure arising due to under-oxidation of ZnO crystals. We also show that the observed defect-related film structure remains stable even after annealing of films under relatively high temperatures (30 min under 450 °C). We assume that both types of films can be of importance for photovoltaic (as contact or active layers, respectively), as well as for chemical or biological sensing, optoelectronics etc.